New guidelines for hospital-acquired pneumonia/ventilator-associated pneumonia: USA vs. Europe. Issue 5 (October 2018) - Martin-Loeches, Ignacio; Rodriguez, Alejandro H.; Torres, Antoni
Abstract : Purpose of review: The International ERS/ESICM/ESCMID/ALAT guidelines for the management of hospital-acquired pneumonia and ventilator-associated pneumonia were published in 2017 whilst the American guidelines for Management of Adults With Hospital-acquired and Ventilator-associated Pneumonia were launched in 2016 by the Infectious Diseases Society of America/ATS. Both guidelines made updated recommendations based on the most recent evidence sharing not only some parallelisms but also important conceptual differences. Recent findings: Contemporary therapy for hospital-acquired pneumonia (HAP) and ventilator-associated pneumonia (VAP) emphasizes the importance of prompt and appropriate antimicrobial therapy. There is an implicit risk, when appropriate means broad spectrum, that liberal use of antimicrobial combinations will encourage the emergence of multidrug resistant (MDR), extensively drug-resistant (XDR) and pandrug-resistant bacteria (PDR) and generate untreatable infections, including carbapenemase resistant infections. Summary: American and European guidelines have many areas of common agreement such as limiting antibiotic duration. Both guidelines were in favour of a close clinical assessment. Neither recommended a regular use of biomarkers but only in specific circumstances such as dealing with MDR and treatment failure. Risk factor prediction for MDR differed and whilst American guidelines focus on organ failure, the European ones did it in local ecology and septic shock.